Integration of bioinformatic and chemoproteomic tools for the study of enzyme conservation in closely related bacterial species - Keller, Laura J; Lakemeyer, Markus; Bogyo, Matthew (Methods in enzymology, 2022)
Activity-based protein profiling (ABPP) is a commonly utilized technique to globally characterize the endogenous activity of multiple enzymes within a related family. While it has been used extensively to identify enzymes that are differentially active across various mammalian tissues, recent efforts have expanded this technique to studying bacteria. As ABPP is applied to diverse sets of bacterial strains found in microbial communities, there is also an increasing need for robust tools for assessing the conservation of enzymes across closely related bacterial species and strains. In this chapter, we detail the integration of gel-based ABPP with basic bioinformatic tools to enable the analysis of enzyme activity, distribution, and homology. We use as an example the family of serine hydrolases identified in the skin commensal bacterium Staphylococcus epidermidis.